Influence of Various Inorganic Cations and Anions on Photocatalytic Degradation of Indigo Carmine - SOHRABI, M.R.; DAVALLO, M.; MIRI, M. (Asian Journal of Chemistry, 2010)
The effect of various inorganic cations and anions on photocatalytic degradation of indigo carmine at optimum conditions have been studied. For achieving optimum conditions several parameters such as pH and the amount of TiO2 on photocatalytic degradation have been investigated. In addition, the effects of UV and TiO2 have been discussed. The maximum efficiency of dye decomposition was achieved at acidic pH of 2 and with 0.4 g of TiO2. The experiments showed that TiO2 and UV light had a negligible effect when used without the addition of the catalysts. It was found that in acidic media addition of various cations and anions resulted in reduction of degradation process.